Fundamental Research Grant Scheme (FRGS) - FRGS17-012-0578. Analyses of infodemiology among parents with chronic disease children in Malaysia for improved public health informatics. - Kartiwi, Mira; Gunawan, Teddy Surya; Ab Rahman, Jamalludin; Ismail, Ahmad Fadzil (2020)
The advancement of technology has changed how parents engage in health information seeking activities through the Internet. Such trends not only shown in developed countries but also most of developing economies as the growth of population access to Internet have been steadily increased in the past ten years. Despite the growing penetration rate, little is known on the extent the Internet is being used by parents to obtain health-related information to improve the wellbeing of their children in developing countries. Five hundred and nineteen responses were collected from parents in selected areas of Klang Valley region in Malaysia. The collected data were analysed by partial least square method of structural equation modelling. The results indicated a positive relationship between information satisfaction and online health information seeking continued use. The moderating role of household income and education are confirmed. The research implications of our results would help medical practitioners and policymaker to design the appropriate supports and awareness programs for parents on the risk and benefits of using online health information.